A History of the History of Programming Languages. - Bergin, Thomas J. (Tim) (Communications of the ACM, 2007)
The article discusses the Association for Computing Machinery's SIGPLAN History of Programming Language conferences. The conferences, which took place in 1978, 1993, and a forthcoming one in June 2007, aim to capture the history of most of the important computer languages by presenting the stories of individuals who were involved in the development of the languages. Conferences have featured talks from John Backus, who explained the origin of FORTRAN, Dennis Ritchie, who discussed the development of C, and Bjarne Stroustrup, who talked about the history of C++.